Análisis crítico sobre la existencia y eficacia de las medidas de protección integral en los procesos de justicia indígena por contravenciones de violencia intrafamiliar. - Rassa Iglesias, Jorge Luis (2023)
The research work that was carried out through a critical analysis has managed to establish the existence of comprehensive protection measures for victims of domestic violence within the indigenous justice system, those that have been implemented after the processing of a dispute within the community so, when establishing its sanction and applying the corresponding healing, the victim is not left unprotected, but the President of the Council, when making the determination or resolution of the case, provides him with support that is the type of family, the same one that is recommended by elders in the community. This type of ancestral justice has been passed down from generation to generation, so it is not possible to establish a written law for each of the conflicts that arises within its territory, but, if the memories of what for the peoples and nationalities is its sentence, which collects the most important and relevant data in this regard, such as: the names of those involved, the type of reparation to the victim and his family, compliance and protection measures so that no what happened is repeated since, its recurrence would result in a stronger sanction and/or banishment or expulsion from the community. The effectiveness of comprehensive protection measures can be established because accompaniment is provided by the godparents of baptism or marriage, these being observers of faithful compliance with what has been decided, the corollary being a peaceful life. and in peace of the family, which is the most important nucleus of the society and the community to which they belong.